Long-term effects of low-molecular-weight organic acids on remobilization of Cd, Cr, Pb, and As in alkaline coastal wetland soil. Issue 1 (1st January 2021) - Sun, Yan; Luo, Ting; Zhong, Siying; Zhou, Feng; Zhang, Yan; Ma, Yurong; Fu, Qiang
ABSTRACT: Low-molecular-weight organic acids (LMWOAs) that have a wide variety of biological activities can affect the mobilization of heavy metals in soil. In this study, the effects of three kinds of LMWOAs on the remobilization of Cd, Cr, Pb, and As were investigated. The results showed that the concentrations of Cr, Pb, and As reached the maximum values at 7 d, and then decreased at 58 d, indicating that the LMWOAs induced the release of these elements from soil. The ability of LMWOAs to affect the mobility of Cr and As followed the order citric acid (1.32 and 2.51mg/L) > malic acid > oxalic acid, while the order for Pb was malic acid (4.49mg/L) > citric acid > oxalic acid. In addition, the sequential extraction indicated that the LMWOAs advanced the reactivation of Pb, Cd, and As, but led to the immobilization of Cr after a long-term reaction.